Identification of Mora in Sokuon, Tan'on, and Chouon by Japanese language learners in Indonesia - Febriyanti, Rike; Febri, Camelia Vonita; Sudiargo, Ary (LITERA, 2024)
Japanese is regarded as mora-timed, while Indonesian is syllable-timed because it provides equal weight and time for all syllables. Indonesian learners are struggling in differentiating one mora and two moras, and single consonant and double consonants. This study investigated Indonesian respondents' ability to identify double consonants (sokuon), short vowels (tan'on) dan long vowels (chouon). 62 Indonesian respondents were involved as they were asked to listen carefully to a set of sounds containing the three distinctive sounds once and to write the sentence they heard. The result showed that 18% of 62 respondents fail to identify the short vowel (tan'on) because they omit certain sounds, change the word form inaccurately and put words in the inaccurate position when they write the sentence. In identifying double consonants (sokuon), 11% of 62 respondents failed because they inaccurately changed the word form when writing the sentence. In identifying long vowels (chouon), only 6% of 62 respondents failed because they added unnecessary sounds and changed the word form inaccurately. In conclusion, although Japanese and Indonesian languages are different in their rhythm classes, Indonesian learners' ability to identify the distinctive sounds of the Japanese language is relatively high although listening to the material more than once.